Phosphatidylserine synthase in the endoplasmic reticulum of Toxoplasma is essential for its lytic cycle in human cells - Dimitrios Alexandros Katelas; Rosalba Cruz-Miron; Ruben D. Arroyo-Olarte; Jos F. Brouwers; Ratnesh Kumar Srivastav; Nishith Gupta (Journal of Lipid Research, 2024)
Glycerophospholipids have emerged as a significant contributor to the intracellular growth of pathogenic protist Toxoplasma gondii. Phosphatidylserine (PtdSer) is one such lipid, attributed to the locomotion and motility-dependent invasion and egress events in its acutely infectious tachyzoite stage. However, the de novo synthesis of PtdSer and the importance of the pathway in tachyzoites remain poorly understood. We show that a base-exchange-type PtdSer synthase (PSS) located in the parasite’s endoplasmic reticulum produces PtdSer, which is rapidly converted to phosphatidylethanolamine (PtdEtn) by PtdSer decarboxylase (PSD) activity. The PSS-PSD pathway enables the synthesis of several lipid species, including PtdSer (16:0/18:1) and PtdEtn (18:2/20:4, 18:1/18:2 and 18:2/22:5). The PSS-depleted strain exhibited a lower abundance of the major ester-linked PtdEtn species and concurrent accrual of host-derived ether-PtdEtn species. Most phosphatidylthreonine (PtdThr) species—an exclusive natural analog of PtdSer, also made in the endoplasmic reticulum—were repressed. PtdSer species, however, remained largely unaltered, likely due to the serine-exchange reaction of PtdThr synthase in favor of PtdSer upon PSS depletion. Not least, the loss of PSS abrogated the lytic cycle of tachyzoites, impairing the cell division, motility, and egress. In a nutshell, our data demonstrate a critical role of PSS in the biogenesis of PtdSer and PtdEtn species and its physiologically essential repurposing for the asexual reproduction of a clinically relevant intracellular pathogen.